EXPANSION OF PROTECTIONIST MEASURES AS A RESULT OF THE GLOBAL ECONOMIC CRISIS - Roganović, Miloš; Popović, Jovanka; Gavrilović, Milan (Poslovna ekonomija, 2017)
We are aware of the fact that the global expansion of crisis has led to an increase in the number of protectionist tendencies in certain countries which have been working on the protection of domestic industry and like that trying to encourage both the growth and the revival which have been deepened by numerous difficulties. By wanting to use protectionist measures to reduce risk, we are wittingly destroying competition and trade, and the crisis is becoming more and more serious.The aim of this paper is focused on the synthesis of theoretical and empirical facts with the aim to identify responses to the following questions: Do protectionist measures represent real danger for the European Union trade market? What is the influence of restrictive measures on the international trade flows?; and Is there a difference in measures carried out by developed and developing economies? The subject of this paper is based on analysis carried out with the help of descriptive and comparative methods. It covers potentially restrictive trade measures introduced in 31 partner countries of the European Union in the period from October 2008 till the end of 2015. The results obtained show that there is no risk of radically turning towards protectionism, but there is still reasonable doubt that permanent consequences on EU trade flows will remain even after the crisis.
Keywords: expansions; restrictions; crisis; TRADE; European Union